An Injectable Fibrin Scaffold Rich in Growth Factors for Skin Repair. (8th February 2021) - Shao, Zhengwei; Lyu, Chengqi; Teng, Lin; Xie, Xuetao; Sun, Jiayue; Zou, Derong; Lu, Jiayu
Abstract : Platelet aggregates, such as PRP, PRF, and CGF, have been used alone or in combination with other grafting materials to enhance restoration outcomes. The process for preparing these autografting materials requires two-step centrifugation or specific centrifuges. In this study, we obtained an injectable fibrin scaffold (IFS) rich in growth factors by one-step centrifugation of whole blood from rabbits. The purpose of this study is to introduce some characteristics of IFS. This scaffold was characterized using various techniques, including Masson's trichrome staining, scanning electron microscopy, porosity measurements, and cell counting. The sustained release of growth factors, including PDGF, VEGF, TGF- β 1, IGF, FGF, and EGF, was quantified using ELISA assay. The obtained IFS was tested for its effects on cell proliferation, extracellular matrix deposition, and full-thickness skin defect repair. The prepared IFS is characterized by a loose fibrin network structure with white blood cells and platelets that slowly release growth factors and can promote the healing of skin defects via the promotion of cell proliferation, collagen deposition, and tissue revascularization. In addition, its liquid properties and porous structure are conducive to its application as a therapeutic component in tissue engineering.